Cell membrane-coated nanoparticles: An emerging antibacterial platform for pathogens of food animals - Altaf, Sidra; Alkheraije, Khalid Ali (Frontiers in Veterinary Science, 2023)
Bacterial pathogens of animals impact food production and human health globally. Food animals act as the major host reservoirs for pathogenic bacteria and thus are highly prone to suffer from several endemic infections such as pneumonia, sepsis, mastitis, and diarrhea, imposing major health and economical loss. Moreover, the consumption of food products from infected animals is the main route by which human beings are exposed to zoonotic bacteria. Thus, there is excessive and undue administration of antibiotics to fight against these virulent causative agents of food-borne illness, leading to the emergence of resistant strains. The increasing prevalence of antibiotic-resistant bacteria and deadly food-borne bacterial infections motivated researchers to discover new alternative therapeutic strategies. One of the successful therapeutic approaches for the treatment of animal infections is the application of cell membrane-coated nanoparticles. Cell membranes of several different types of cells including platelets, red blood cells, neutrophils, cancer cells, and bacteria are being wrapped over the core of nanoparticles to prepare biocompatible and biodegradable nanoformulations. This diversity of cell membrane selection and together with the possibility of combining with an extensive range of nanoparticles, has opened a new opportunistic window for the development of more potentially effective, safe, and immune-evading nanoformulations, as compared to the conventionally used bare nanoparticle. This article will elaborately discuss the discovery and development of novel bioinspired cell membrane-coated nanoformulations against several pathogenic bacteria of food animals such as Klebsiella pneumonia, Escherichia coli, Staphylococcus aureus, Salmonella enteritidis, Campylobacter jejuni, Helicobacter pylori, and Group A Streptococcus and Group B Streptococcus.